Utilizing Carbon Dots Derived from Waste Face Masks for Pentachlorophenol Detection - Ozturk, Dilek; Durmuş, Mahmut (Springer/Plenum Publishers, 2025)
Pentachlorophenol is a very toxic chemical that is used as a pesticide, fungicide, herbicide, wood preservative, etc., and it should be monitored in terms of human health and environmental production. Another environmental problem is the increase in the use of facemasks, especially during the COVID-19 pandemic. This study provides a value added chemicals to sustainability of recycling process. Fluorescent carbon dots (CDs) were synthesized from waste facemasks and investigated their fluorescence sensor performances. UV-Vis and fluorescence spectra of the synthesized carbon dots were recorded in different organic solvents. The sensor properties of these carbon dots against pesticides were investigated, and a 'turn-off' response was observed toward pentachlorophenol. The limit of detection was found 8.5 mu M in the linear range from 43.3 mu M to 375 mu M. This study showed that waste plastics such as facemasks can be recycled to obtain carbon dots, which are used in different technological areas such as photocatalysis, bioimaging, etc., as well as in sensors.
Keywords: Waste facemask; Carbon dot; Pentachlorophenol; Fluorescence sensor